Kesetaraan Di Muka Hukum Bagi Penyandang Disabilitas (Analisis Putusan Nomor 28/Pid.B/Pn.Skh/2013) - Siti Nurhayati (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
The right on the same position on the law means that every citizens including disabilities persons have the same change to use their rights regulated by the institution. Indonesia government has signed Convention on the Rights of Persons with Disabilities in March 30, 2007 in New York. That even shows the strong intention of Indonesia country to respect, save, fulfill, and develop the disabilities persons’ right to fulfill the welfare of the disabilities persons. There is a case happened in Sukaharjo in the decision No. 18/Pid.B/PN.SKH/2013 about a crime defeated the disabilities person. This study employed library research design. The finding shows that the judges in the decision Nomor 28/Pid.B/PN.SKH state that the defendant convicted 8 years 6 months. The decision can be used as jurisprudence for other judges in examining the same case in order to avoid criminal disparity. In a further development, the criminal appeals to the High Court in Central Java, and in the High Court, Decision No. 244 / Pid 2013 / P.T.Smg actually strengthens the High Court Decision Sukoharjo with 10 years prison. Based on this decision it should increase the capacity of law enforcement agencies in the fulfillment of the right to a fair trial for persons with disabilities must be done. It aims to introduce the concept of disability to law enforcement officials, provide an understanding of human rights, especially the rights of persons with disabilities to law enforcement officials, as well as provide expertise (skills) to law enforcement authorities on the way and methods to fulfill the accessibility of persons with